1993
DOI: 10.1034/j.1399-3054.1993.870409.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteins accumulate in the apoplast of winter rye leaves during cold acclimation

Abstract: 1993. Proteins accumulate in the apoplast of winter rye leaves during cold acchmation. -Physiol. Plant. 87: 499-507.During cold acclimation, winter rye {Secale cereale L.) plants develop the ability to tolerate freezing temperatures by forming ice in intercellular spaces and xylem vessels. In this study, proteins were extracted from the apoplast of rye leaves to determine their role in controlling extracellular ice formation. Several polypeptides in the 15 to 32 kDa range accumulated in the leaf apoplast durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
(22 reference statements)
0
15
2
1
Order By: Relevance
“…4). The level of freezing tolerance in the suspension cells in this work was lower than we expected based on the concentration of AFPs found in maximally freezing‐tolerant winter rye leaves (Marentes et al 1993). This suggests that AFPs do not occur as oligomeric complexes in suspensions, as they do in the intact leaves (Yu and Griffith 1999), and that other intracellular and/or extracellular solutes than AFPs, share the responsibility for freezing tolerance with AFPs in winter rye cells.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…4). The level of freezing tolerance in the suspension cells in this work was lower than we expected based on the concentration of AFPs found in maximally freezing‐tolerant winter rye leaves (Marentes et al 1993). This suggests that AFPs do not occur as oligomeric complexes in suspensions, as they do in the intact leaves (Yu and Griffith 1999), and that other intracellular and/or extracellular solutes than AFPs, share the responsibility for freezing tolerance with AFPs in winter rye cells.…”
Section: Discussioncontrasting
confidence: 60%
“…5). The concentration of apoplastic protein used in this experiment was chosen on the basis of our pilot experiments and previously reported concentrations of AFPs in CA rye leaves (Marentes et al 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of ice-binding activity in transgenic lines was observed in crude cell extracts containing both intracellular and extracellular components, but also in the apoplastic extracts of IBP knockdowns (Fig 10). Most plant IBPs have been shown to localize to the apoplast [7,14,20,5253] and recent research has demonstrated that localization of IBPs to the extracellular space may be required for full freeze protection [20]. In addition to the identification of putative extracellular signal peptides in the N-terminal domain of all 7 Bd IRIs (Fig 1), the presence of IRI and TH activity, as well as ice shaping in the apoplastic extracts of wild-type B .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that stress conditions greatly affect the composition of apoplastic proteins both qualitatively and quantitatively [12]. There is strong evidence that apoplast proteins are greatly altered in response to salt [13], chilling [14], salicylic acid [15], metal toxicity [16] and pathogen invasion [17]. When compared to the intracellular signaling pathway components and effectors, the roles of plant apoplastic proteins have been obviously ignored in analyzing the plant stress response.…”
Section: Introductionmentioning
confidence: 99%